PROTOTYPE SISTEM KEAMANAN RUMAH BERBASIS MULTI-SENSOR DAN NOTIFIKASI SMS MENGGUNAKAN ESP32 - Arif Paulus W. Hutagaol; Nicolaus Fidal Diaz Manurung; Wendy Panglima Sikop Pasaribu; Eka Dodi Suryanto; Dian Putra Saragi (JOURNAL SAINS STUDENT RESEARCH, 2026)
The rapid development of embedded systems technology has driven the advancement of more effective and autonomous home security systems, particularly in environments with limited internet access. Potential risks such as fire, gas leakage, and physical intrusion require an early detection system that can operate in real time and reliably. This study aims to design and implement a prototype of a home security system based on ESP32 using a multi-sensor approach and SMS-based notification. An experimental method was employed, including system design, hardware and software implementation, and performance testing. The proposed system integrates a PIR sensor for motion detection, an MQ-2 sensor for gas and smoke detection, a flame sensor for fire detection, and an SW-420 vibration sensor for physical disturbances, supported by a SIM800L GSM module for communication. The results show that the system is capable of detecting hazardous conditions in real time with good responsiveness, where the flame sensor has the fastest response time of approximately ±1 second, PIR and vibration sensors respond within ±1–2 seconds, and the MQ-2 sensor requires ±2–5 seconds depending on gas concentration. The system also successfully sends SMS notifications with an average delay of 5–10 seconds depending on network signal quality. Overall, the system demonstrates stable and effective performance, making it a reliable and cost-efficient embedded-based home security solution that does not depend on internet connectivity and is suitable for various environmental conditions.